The Changing Value Relevance of Accounting Information: An Overview - Siregar, Hilda Octavana; Nurharjanti, Nashirotun Nisa (Riset Akuntansi dan Keuangan Indonesia, 2021)
This article aims to provide an overview of the value relevance of accounting information development for investors and creditors who are the primary users of financial statements. The traditional approach views stock prices as value relevance of the focal accounting information that can reflect the company’s condition. However, during the last 2 (two) decades, the value relevance of accounting information has varied more, such as cash flow, operating profit, and tangible assets. Furthermore, value relevance for creditors is bankruptcy prediction, bond rating, loss frequency, fair value measurement, and changes in the company’s accounting method. The change in the value relevance of accounting information is essential in increasing its usefulness and can contribute to research on the usefulness of accounting information in the future.